The concept of good faith in the law of contract: Redefined and reimagined (The Pretoria Student Law Review, 2025)
In civil, and some common law, jurisdictions, good faith is recognised as a fundamental principle informing the law of contract and is often invoked by some law courts to set aside contracts found not to have been concluded in good faith. It is a counterpoise to the dominant idea of freedom of contract. Whilst it cannot be denied that the Constitution of the Republic of South Africa, 1996 has had a positive impact on the doctrine of good faith in South African jurisprudence, good faith still has a larger role to play to ensure justice and fairness whilst preventing commercial immorality. It is, therefore, against this backdrop that this paper will examine the role of good faith and fairness in South African contract law. it is found that the concept of good faith plays an important role in contract law as it can be a determining factor in the validity or invalidity of a contract. It is inextricably linked to the concept of fairness and has the effect of counteracting contracts that are unfair or unconscionable. The article further looks at the role of good faith in the contract law of foreign jurisdictions and sets out the lessons we can draw from these jurisdictions.